Investigating employee performance in higher education: The role of satisfaction and commitment - Zafira Yasmin; Edi Suryadi; Budi Santoso; Suparno Suparno (International Journal of Evaluation and Research in Education (IJERE), 2023)
The rapid transformation of education requires performance and innovation. This study aimed to examine the interconnectedness between organizational commitment (OC), job satisfaction (JS), and employee performance (EP) in higher education in Indonesia. EP is measured by how well you handle critical emergencies, how well you solve creative problems, how well you manage work stress, how well you handle uncertain and unpredictable work situations, and how well you adapt to other people. OC is measured by the strong desire to be an employee, the desire to work hard, acceptance of organizational values, acceptance of organizational goals, and work loyalty. JS is measured by the work itself, wages, promotion opportunities, supervision, and colleagues. The population in this study were all 150 employees of the Archive Bureau in Educational Colleges in Indonesia. In this study, researchers used the saturated sampling method as the basis for sampling, where all 150 members of the population were used as samples. A deeper comprehension of the connections between the variables was achieved by quantitatively applying structural equation modeling based on AMOS 21. The findings indicate that organizational commitment and job satisfaction positively influence employee performance in higher education in Indonesia. Indeed, job satisfaction among employees can enhance their performance. This study helps organizations perform better during COVID-19, particularly in higher education. The researcher suggests that additional researchers conduct larger-scale research on improving performance in areas like innovation and productive behavior.